Comissão Nacional da Verdade: limites e desafios - Pereira, Bruna Ferrari (2016)
In this research we conducted a rigorous study of the final report of the National Truth Commission, seeking to understand how the current political and social situation in the country was limited and overshadowed the gains brought by this Commission. This research had as material beyond the final report, the military's statements given to the Commission, the newspaper reports on the subject and a vast literature on the subject. From this material, the main objective of this research was to analyze how civil-military relations during the work of CNV are directly related to the permanence of the dictatorial legacy in our current democracy.